Evaluating Human Resource to Implement SCP Using Grey Relational Analysis - Uniyal, Surbhi; Mangla, Sachin Kumar; Patil, Pravin P. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927);" role="presentation">In order to overcome the <span dir="ltr" style="left: calc(var(–scale-factor)*175.82px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926513);" role="presentation">situation of misuse of earth and society, a large pressure is building arou<span dir="ltr" style="left: calc(var(–scale-factor)*471.58px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934959);" role="presentation">nd all the factors <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*335.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946851);" role="presentation">of the human<span dir="ltr" style="left: calc(var(–scale-factor)*127.10px); top: calc(var(–scale-factor)*335.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942041);" role="presentation">kind to successfully adopt and implement sustainable manufacturing at various stages of the supply <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918604);" role="presentation">chains. In the present study s<span dir="ltr" style="left: calc(var(–scale-factor)*191.21px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.09158);" role="presentation">ix <span dir="ltr" style="left: calc(var(–scale-factor)*202.25px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932651);" role="presentation">factors of human <span dir="ltr" style="left: calc(var(–scale-factor)*274.73px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.871115);" role="presentation">resources <span dir="ltr" style="left: calc(var(–scale-factor)*315.77px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923186);" role="presentation">are identified and categorized <span dir="ltr" style="left: calc(var(–scale-factor)*439.75px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999855);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*450.70px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*466.18px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937486);" role="presentation">Indian automobile <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925381);" role="presentation">industry <span dir="ltr" style="left: calc(var(–scale-factor)*107.54px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930377);" role="presentation">context. The Grey relational analysis (GRA) technique is u<span dir="ltr" style="left: calc(var(–scale-factor)*346.39px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977614);" role="presentation">tilized <span dir="ltr" style="left: calc(var(–scale-factor)*374.23px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901514);" role="presentation">to evaluate the success factors. The Grey <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928509);" role="presentation">relational analysis (GRA) is a qualitative and quantitative approach that <span dir="ltr" style="left: calc(var(–scale-factor)*365.83px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.879548);" role="presentation">is used <span dir="ltr" style="left: calc(var(–scale-factor)*396.79px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977282);" role="presentation">widely <span dir="ltr" style="left: calc(var(–scale-factor)*426.67px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931282);" role="presentation">as a multi-<span dir="ltr" style="left: calc(var(–scale-factor)*469.78px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939097);" role="presentation">criterion decision <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931792);" role="presentation">making <span dir="ltr" style="left: calc(var(–scale-factor)*108.24px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01559);" role="presentation">(MCDM) <span dir="ltr" style="left: calc(var(–scale-factor)*152.97px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89679);" role="presentation">method <span dir="ltr" style="left: calc(var(–scale-factor)*189.17px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932477);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*203.32px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902183);" role="presentation">solve <span dir="ltr" style="left: calc(var(–scale-factor)*230.66px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*249.12px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917107);" role="presentation">complicated <span dir="ltr" style="left: calc(var(–scale-factor)*304.28px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921896);" role="presentation">relationship <span dir="ltr" style="left: calc(var(–scale-factor)*357.64px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904836);" role="presentation">problems <span dir="ltr" style="left: calc(var(–scale-factor)*401.15px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925415);" role="presentation">having <span dir="ltr" style="left: calc(var(–scale-factor)*434.61px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9022);" role="presentation">uncertainties. <span dir="ltr" style="left: calc(var(–scale-factor)*494.86px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*516.80px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931652);" role="presentation">factor ‘<span dir="ltr" style="left: calc(var(–scale-factor)*75.26px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949458);" role="presentation">Commitment and transparency of stakeholders towards standardization of products<span dir="ltr" style="left: calc(var(–scale-factor)*423.67px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996085);" role="presentation">’ achieves the first position <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919799);" role="presentation">whereas factor ‘<span dir="ltr" style="left: calc(var(–scale-factor)*136.70px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912206);" role="presentation">Trust among the members of <span dir="ltr" style="left: calc(var(–scale-factor)*255.89px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*270.77px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921349);" role="presentation">supply chain<span dir="ltr" style="left: calc(var(–scale-factor)*321.91px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939801);" role="presentation">’ stays behind at last position. This work is helpful for <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888703);" role="presentation">managers and practitioners to create a <span dir="ltr" style="left: calc(var(–scale-factor)*225.89px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893762);" role="presentation">coordinated and focused <span dir="ltr" style="left: calc(var(–scale-factor)*326.11px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917515);" role="presentation">system within the supply chain.